Structure and functional properties of prokaryotic small noncoding RNAs - Mikulík, K (Folia microbiologica, 2003)
Most biochemical, computational and genetic approaches to gene finding assume the Central Dogma and look for genes that make mRNA and have ORFs. These approaches essentially do not work for one class of genes--the noncoding RNA. In all living organisms RNA is involved in a number of essential cell processes. Functional analysis of genome sequences has largely ignored RNA genes and their structures. Different RNA species including rRNA, tRNA, mRNA and sRNA (small RNA) are important structural, transfer, informational, and regulatory molecules containing complex folded conformations that participate in recognition and catalytic processes. Noncoding RNAs play an number of important structural, catalytic and regulatory roles in the cell. The size of the sRNA genes ranges from 70 to 500 nucleotides. Several transcripts of these genes are processed by RNAases and their final products are smaller. The encoding genes are localized between two ORFs and do not overlap with ORFs on the complementary DNA strand. As aptamers, some sRNA bind small molecular components (metal ions, peptides and nucleotides). This review summarizes recent data on the functions of prokaryotic sRNAs and approaches to their identification.
Keywords: konformace nukleové kyseliny; nekódující RNA; Prokaryotic Cells; Bacteria; RNA, Bacterial; Base Sequence; bakteriální RNA; sekvence nukleotidů; molekulární modely; prokaryotické buňky; RNA, Untranslated; Nucleic Acid Conformation; Molecular Sequence Data; Models, Molecular; molekulární sekvence - údaje